Warung Kopi dan Santri; Religion in Secularcapes (Institut Agama Islam Negeri Kendari, 2023)
The interaction between coffee shops and Muslims has led to studies on history, philology, symbolic interaction, and pluralism. Although research on coffee shops and Muslims has emerged, there is still no one who looks at it from the perspective of religioscapes. This study aims to examine the interaction of santri in public spaces and how the impact is caused from the perspective of religioscapes. This research uses Spradley's ethnographic method, intending to analyze the phenomenon of santribehavior in coffee shops in detail. Researchers become part (live in) so that they can elaborate on the various meanings of ways of thinking and behaving in understanding human clumps. Claudia Seise's concept of Religioscapes is used as an analytical method in describing the religious state of santri in Warung Kopi Yogyakarta. This research shows that religious practices that occur in secular places, including the recitation of shalawat burdah and the recitation of yellow books on the themes of fiqh, nahwu, and tasawwufthat are routinely carried out by santri, can influence other individuals, especially from non-santri, resulting in religion in secularcapes. Coffee shops as places that are initially neutral/secular become spaces for certain religious practices, which we call religion in secularscapes. This research implies that santri can form new religious spaces, or new religioscapes in secular places, where neutral spaces become sacred and religioscapes of this model do not have the main authority, but have diffuse authority.